Disaster Mitigation Through Community Education: A Study of Evacuation Knowledge ln Lapindo Mud Area - Aulady, Mohamad Ferdaus Noor; Andhima, Rizqa Nurun Dina (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
The phenomenon of the Lapindo Mudflow that occurred on May 29, 2006, in Sidoarjo, East Java Province has entered its 17th year after the disaster with a continuous overflow until now. One of the disaster mitigation methods to handle the threat of wider mudflow to more densely populated areas is with the construction of embankments. Glagaharum Village on Porong is directly adjacent to the outer barrier with a distance of ± 500 meters, and between the village and the embankment is only a meter-wide tributary before reaches the village road. This research was arranged descriptively with a quantitative method. This method was used to find out the community's knowledge about evacuation routes and places through questionnaires. Researchers used the parameters of age, gender, and education as a binary logistic regression test. The binary logistic regression test showed that the education parameter had more influence on knowledge of evacuation locations; next was gender, and lastly was age. Education influences education level, literacy level, and critical thinking skills. Meanwhile, the female gender had difficulties regulating emotions when circumstances were urgent. So, the importance of increasing literacy and adding special training for women was needed to increase equality in the knowledge of evacuation locations.